2022
DOI: 10.1002/ange.202207587
|View full text |Cite
|
Sign up to set email alerts
|

Capture of Hydroxyl Radicals by Hydronium Cations in Water Microdroplets

Abstract: Despite the high stability of bulk water, water microdroplets possess strikingly different properties, such as the presence of hydroxyl radicals (OH⋅) at the air–water interface. Previous studies exhibited the recombination of OH⋅ into H2O2 molecules and the capture of OH⋅ by oxidizing other molecules. By spraying pure water microdroplets into a mass spectrometer, we detected OH⋅ in the form of (H4O2)+ that is essentially OH⋅−H3O+, a hydroxyl radical combined with a hydronium cation through hydrogen bonding. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…It is postulated that there is a high electric field (∼10 9 V/m) at the microdroplets’ surface due to either the formation of electric double layers or the alignment of the free O–H bonds of water molecules. This high field can even pull electrons out of hydroxide ions, resulting in an electron and a hydroxyl radical. The electron is responsible for the above-mentioned reduction reactions, and the hydroxyl radical can cause oxidation reactions or combine with others to form H 2 O 2 . In some cases, reduction by the electron and oxidation by OH were observed simultaneously for the same substrate molecules . It was also observed that, on the aerial surface of air bubbles in water, the oxidation potentials of OH – to OH occurred 0.7 V below redox tabled values as measured by electrochemical methods, so it should be easier for OH – to give up the electron at the air–water interface compared to the bulk.…”
mentioning
confidence: 99%
“…It is postulated that there is a high electric field (∼10 9 V/m) at the microdroplets’ surface due to either the formation of electric double layers or the alignment of the free O–H bonds of water molecules. This high field can even pull electrons out of hydroxide ions, resulting in an electron and a hydroxyl radical. The electron is responsible for the above-mentioned reduction reactions, and the hydroxyl radical can cause oxidation reactions or combine with others to form H 2 O 2 . In some cases, reduction by the electron and oxidation by OH were observed simultaneously for the same substrate molecules . It was also observed that, on the aerial surface of air bubbles in water, the oxidation potentials of OH – to OH occurred 0.7 V below redox tabled values as measured by electrochemical methods, so it should be easier for OH – to give up the electron at the air–water interface compared to the bulk.…”
mentioning
confidence: 99%
“…In the case to oxidize aromatic rings, it showed characteristic of adding •OH radicals onto the compounds, reacting with a compound by H abstraction or addition. (37,38) 6…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, the strong electric eld established by the microdroplet electrical double layer (also reported to be in the order of 1 V nm −1 ) was recently postulated by Zare and others to generate hydroxyl radicals in the liquid phase which contributed to the observed spontaneous formation of hydrogen peroxide. 25,34 Isotope labeling method was used to determine the origin of the oxygen atom. The analyte was L-phosphatidylcholine (PC 18 : 1/18 : 1) with two double bonds (one at each fatty acid chain).…”
Section: Source Of Oxygen Atomsmentioning
confidence: 99%